FORMULATION AND OPTIMIZATION OF CERITINIB LOADED NANOBUBBLES BY BOX-BEHNKEN DESIGN - MURALIKRISHNA, PONNAGANTI; BABU, ANCHA KISHORE; MAMATHA, PALANATI (International Journal of Applied Pharmaceutics, 2022)
Objective: Ceritinib is an anaplastic lymphoma kinase (ALK) inhibitor used to treat lung cancer. In the current research, the ceritinib-loaded nanobubbles were prepared by using perfluorobutane for inner core and medium molecular weight chitosan for the shell. Methods: A 33Box-Behnken design was used to determine the influence of L-α-Phosphatidylcholine (A), the concentration of chitosan (B) and concentration of palmitic acid (C) factors affecting particle size, and polydispersity index. The individual effects of these factors on particle size and polydispersity index were depicted in perturbation plot, response surfaces and counterplots based on Derringer’s desirability approach. Results: The extreme desirability function value was obtained at A: 1.31 % w/v, B: 3.00 % w/v, C: 1.5 % W/V. Three batches of formulation were prepared in accordance to the desirability function and evaluated. TEM images revealed the superficial morphology and core-shell structure of nanobubbles in the size range of 150-200 nm. Nanobubbles were able to load ceritinib with an encapsulation efficiency of 79.12 % and a loading capacity of 19.2 %. The nanobubbles released about 95.67 % drug in 24h. The in vitro cellular uptake study results show the enhanced cellular uptake of ceritinib with ultrasound from nanobubbles. In vitro cytotoxicity study results indicated that ultrasound-assisted nanobubbles can effectively release in the cells with high sensitivity. Conclusion: Chitosan-based ceritinib nanobubbles, therefore, offer a remarkable tool for the development of ultrasound-responsive formulations that deliver drugs to the target.